Resistance through Connections, Communities and Friendships: Interrelational Possibilities of Educational Curriculum Design - Selvarajah, Abarna (Comparative and International Education / Éducation comparée et internationale)

(untitled) (University of Western Ontario, 2023)
This paper examines the transformational possibilities of educational curriculum design in fostering interrelational solidarities among mature migrant and diaspora women. It offers a brief introduction to an emerging doctoral project that engages with the educational experiences of mature migrant and diaspora women in Canada. Throughout a migrant woman’s displacement and “settlement” journey, friendships emerge as a starting point through which some women start to construct their agentic selves within and outside their homes, partners, and diasporic community. These friendships allow for a transnational self to emerge, one that can move beyond identification as the primary location for struggle, and towards shared, but different, experiences of oppression. By resisting neoliberal and multicultural immigration policies that isolate mature immigrant women and reproduce violence, these connections, communities, and friendships push settlement education systems to reckon with complicated, yet symbiotic experiences of migrant and diaspora women.